How Not to be the Perfect Teenager - Brave, Ulysses (London Star Fire Books, 2007)
The teenage years can be a nightmare for all involved. Moody, hormonal and 'misunderstood', teenagers are a handful. Containing advice inspired by the animal world, this book includes photographs and words of wit and wisdom
Include Color Illustration
Keywords: Teenagers--Conduct of life -- Adolescent psychology